2021
DOI: 10.1093/eurjcn/zvab015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity improvement after cardiac rehabilitation following myocardial infarction and its association with long-term cardiovascular events

Abstract: Aims  Cardiovascular rehabilitation (CR) improves aerobic capacity and quality of life in patients after myocardial infarction (MI). The aim was to examine the associations between exercise capacity improvement and different clinically relevant cardiovascular events. Methods and results  This was a registry-based study of post-MI patients, referred to CR. All patients were submitted to exercise testing before and after CR (36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Exercise-based cardiac rehabilitation reduces cardiovascular morbidity and mortality in patients with coronary artery disease (CAD) [ 1 , 2 , 3 ]. Ample evidence suggests that exercise training improves markers of cardiovascular health such as risk factors, exercise capacity, vascular function and heart rate variability (HRV); however, the vast majority of exercise studies in patients with CAD employ land-based aerobic dynamic modalities, such as cycling or treadmill walking [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise-based cardiac rehabilitation reduces cardiovascular morbidity and mortality in patients with coronary artery disease (CAD) [ 1 , 2 , 3 ]. Ample evidence suggests that exercise training improves markers of cardiovascular health such as risk factors, exercise capacity, vascular function and heart rate variability (HRV); however, the vast majority of exercise studies in patients with CAD employ land-based aerobic dynamic modalities, such as cycling or treadmill walking [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-based cardiac rehabilitation reduces cardiovascular morbidity and mortality in patients with coronary artery disease (CAD) [ 1 , 2 , 3 ]. Ample evidence suggests that exercise training improves markers of cardiovascular health such as risk factors, exercise capacity, vascular function and heart rate variability (HRV); however, the vast majority of exercise studies in patients with CAD employ land-based aerobic dynamic modalities, such as cycling or treadmill walking [ 3 , 4 , 5 ]. Conversely, aquatic exercise (such as swimming or water aerobics training)—while a popular exercise modality—remains rarely provided or even discouraged, mainly because of its perceived risks (i.e., unfavorable hemodynamic response to water immersion and temperature, possibly yielding ventricular dysfunction and/or dysrhythmias in cardiac patients) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac rehabilitation reduces risk factors, and increases the aerobic fitness, medication adherence, and survival after percutaneous coronary intervention and coronary artery bypass graft surgery ( Colantonio et al, 2017 ; Rosenson et al, 2017 ). Moreover, it improves survival and reduces risk of recurrent MI in patients with acute MI (AMI) ( Novaković et al, 2022 ). A previous meta-analysis comprising 63 trials and 14,486 patients assigned to exercise-based cardiac rehabilitation or no referral following MI or revascularization, reported that cardiac rehabilitation was associated with a lower risk of cardiovascular death [relative risk (RR) 0.74, 95% CI 0.64–0.86] and hospital readmission (RR 0.82, 95% CI 0.70–0.96) at 12-months ( Anderson et al, 2016 ).…”
Section: Role Of Exercise In Cardiac Rehabilitation Of Patients With ...mentioning
confidence: 99%
“… 3 Cardiac rehabilitation in postmyocardial infarction improve lifestyle habits such as physical activity and dietary intake, and has also shown positive effects on blood lipids, blood pressure and smoking. 4–6 In a small randomised trial, cardiac rehabilitation programme for patients with myocardial infarction or who had undergone coronary artery by-pass graft surgery (CABG), focusing on stress management, physical exercise and dietary intake, reduced morbidity and hospitalisation for CHD. 7 Attendance in cardiac rehabilitation programme has long-term effects on survival among patients who have undergone CABG with reduced 10-year all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cardiac rehabilitation in postmyocardial infarction improve lifestyle habits such as physical activity and dietary intake, and has also shown positive effects on blood lipids, blood pressure and smoking. [4][5][6] In a small randomised trial, cardiac rehabilitation…”
Section: Introductionmentioning
confidence: 99%